Association between mean arterial pressure and clinical outcomes among patients with heart failure - Qi Gao; Yuxin Lin; Ruqi Xu; Yuping Zhang; Fan Luo; Ruixuan Chen; Pingping Li; Sheng Nie; Yanqin Li; Licong Su (ESC Heart Failure, 2023)
Abstract Aims Mean arterial pressure (MAP) is widely used for evaluating organ perfusion, but its impact on clinical outcomes in patients with heart failure (HF) remains poorly understood. The aim of this study is to investigate the relationship between MAP and all‐cause mortality and readmission in patients with HF. Methods and results We retrospectively analysed data from PhysioNet, involving 2005 patients with HF admitted to Zigong Fourth People's Hospital between 2016 and 2019. The primary outcomes were composite outcomes of all‐cause mortality and readmission at 3 and 6 months. The secondary outcomes were readmission at 3 and 6 months. Multivariate‐adjusted Cox regression models, restricted cubic spline curves (RCS), and propensity score matching (PSM) were used to explore the relationship between MAP and clinical outcomes. Among 2005 patients with HF [≥70 years, 1460 (72.8%); male, 843 (42.0%)], the incidence of primary outcome at 3 months was 33.4% (223/668), 24.4% (163/668), and 22.7% (152/669), and at 6 months, it was 47.5% (317/668), 38.5% (257/668), and 38.0% (254/669) across MAP tertiles [from Tertile 1 (T1) to Tertile 3 (T3)], respectively. The RCS showed an ‘L‐shaped’ relationship between MAP and primary or secondary endpoints. Multivariate‐adjusted Cox models showed that a higher MAP was significantly associated with a lower risk of composite endpoints at 3 months [adjusted hazard ratio (aHR) 0.75, 95% confidence interval (CI) 0.61–0.92, P = 0.006, Tertile 2 (T2); aHR 0.69, 95% CI 0.56–0.86, P = 0.001, T3] and 6 months (aHR 0.79, 95% CI 0.67–0.93, P = 0.005, T2; aHR 0.77, 95% CI 0.64–0.91, P = 0.003, T3) compared with T1. After 1:1 PSM, the effect of maintaining a relatively higher MAP was slightly attenuated. Threshold analyses indicated that per 10 mmHg increase in MAP, there was a 21% and 14% decrease in composite endpoints at 3 and 6 months, respectively (aHR 0.79, 95% CI 0.69–0.91, P = 0.001), and 6 months (aHR 0.86, 95% CI 0.77–0.97, P = 0.013) in patients with MAP ≤ 93 mmHg. The associations were consistent in readmission (secondary outcomes), various subgroups, and sensitivity analysis. Conclusions A higher MAP was associated with a lower risk of a composite of all‐cause mortality and readmission. Maintaining a relatively higher MAP could potentially improve the clinical prognosis for patients with HF.